Narcolepsy as an Immune-Mediated Disease - De la Herrán-Arita, Alberto K. (Hindawi Publishing Corporation, 2014)
Narcolepsy is a neurological disorder characterized by excessive daytime sleepiness, cataplexy, hypnagonic hallucinations, sleep paralysis, and disturbed nocturnal sleep patterns. This disease is secondary to the specific loss of hypothalamic hypocretin (orexin)-producing neurons in the lateral hypothalamus. An autoimmune basis for the disease has long been suspected based on its strong association with the genetic marker DQB1∗06:02, and current studies greatly support this hypothesis. Narcolepsy with hypocretin deficiency is associated with human leukocyte antigen (HLA) and T cell receptor (TCR) polymorphisms, suggesting that an autoimmune process targets a peptide unique to hypocretin-producing neurons via specific HLA-peptide-TCR interactions. This concept has gained a lot of notoriety after the increase of childhood narcolepsy in 2010 following the 2009 H1N1 pandemic (pH1N1) in China and vaccination with Pandemrix, an adjuvanted H1N1 vaccine that was used in Scandinavia. The surge of narcolepsy cases subsequent to influenza A H1N1 infection and H1N1 vaccination suggests that processes such as molecular mimicry or bystander activation might be crucial for disease development.